Social responsibility of organization towards new and radical market actors - Dereń, Aldona Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The purpose of the article is an attempt to outline the problems related to the participation of new and radical social communities in the market game, such as: Internet communities, members of the precariat, refugees, immigrants and terrorists. These communities have not been the object of thorough research and analysis related to the theory of management yet. Most of the radical market actors were developed in a spontaneous manner or as a result of globalization processes taking place in the contemporary world. This is a specific challenge for organizations, especially for those which implement a strategy based on social responsibility. Our recommendation includes social communication and co-existence as the basis and framework for an organization which is socially responsible. These are frameworks making it possible to shape an individual business ecosystem in which it is necessary to establish specific relations even with the most radical actors of the contemporary market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 464, s. 20-30
Keywords: social responsibility; market actor; Internet community; precariat; refugee; immigrant; terrorist; odpowiedzialność społeczna; aktor rynkowy; społeczność internetowa; prekariusz; uchodźca; imigrant; terrorysta